Evaluation of the Level of Awareness and Knowledge of Self-Examination and Mammography Examination among a Group of Libyan Women in Misurata City - Mohamed Ben Taher; Mohamed Sherfad; Khalid Abufalgha (AlQalam Journal of Medical and Applied Sciences, 2024)
Cancer is one of the significant public health problems in the world. Also, breast cancer is a malignant cell, which may start in the breast tissue. Breast self-examination (BSE) is a simple, non-invasive, and low-cost, to detect any changes in breast tissue at an early time. This study aims to assess the awareness and knowledge of BSE and mammography examination among females with different levels of education in city of Misurata-Libya. This study used validated questionnaire divided into two sections. The data collection was from December 2021 to May 2022. 550 questionnaires were distributed to adult volunteers who attending an out-patient clinic at a hospital clinic and/or students and teaching staff at Faculty of medical technology in Misurata. There was a high return rate with 460 (83.63%) returned in total. Statistical analyses were performed using the Statistical Package for the Social Sciences, version 24 (IBM, Armonk NY). Statistical significance was set at p < 0.05. The study showed that 14.8% of the participants practiced BSE practice as a monthly routine. However, the majority of respondents 251 (54.6%) in this study were rarely do the BSE practice. 92.17% of participants had very low knowledge about the mammography examination. The results of this study have demonstrated the extremely low level of awareness of breast mammography examination and performing BSE was particularly low among Misurata Libyan woman community. يعد السرطان أحد مشاكل الصحة العامة في العالم. كما أن سرطان الثدي عبارة عن خلية خبيثة قد تبدأ نموها في أنسجة الثدي. ويعتبر الفحص الذاتي للثدي فحص بسيط وغير جراحي ولا يوجد به تكلفة مالية حيث تقوم به المراءة لاكتشاف أي تغيرات في أنسجة الثدي مبكرا. حيث تهدف هذه الدراسة إلى تقييم الوعي والمعرفة بمرض سرطان الثدي وكذلك تقييم المعرفة بالفحص بالتصوير الشعاعي للثدي بين الإناث بمستويات تعليمية مختلفة في مدينة مصراتة-ليبيا. حيث استخدمت هذه الدراسة استبيانًا تم التحقق منه مقسمًا إلى قسمين. وتم جمع البيانات في الفترة ما بين ديسمبر 2021 إلى مايو 2022. حيث تم توزيع 550 استبيانًا على المشاركات البالغات اللاتي كانت لهن مواعيد بالعيادات الخارجية بالمستشفى وكذلك الطالبات وأعضاء هيئة التدريس الإنات في كلية التقنية الطبية بمصراتة. حيث أظهرت هذه الدراسة معدل استجابة مرتفع بلغ إجمالي العائدات 460 (83.63٪). ولقد تم إجراء التحليلات الإحصائية باستخدام برنامج التحليل الإحصائي الإصدار 24 (IBM, Armonk NY) (SPSS وتم تحديد الأهمية الإحصائية عند. P <0.05حيث أظهرت هذه الدراسة أن 14.8% من المشاركات أجرن الفحص الذاتي للثدي بشكل روتيني شهريا ومع ذلك، فإن غالبية المشاركات 251 (54.6٪) في هذه الدراسة كنا نادرا ما يقمنا بالفحص الذاتي للثدي. 92.17% من المشاركات لديهن معرفة منخفضة جدًا بفحص التصوير الشعاعي للثدي. أظهرت نتائج هذه الدراسة أن مستوى الوعي كان منخفض للغاية حول فحص الثدي بالأشعة السينية وكذلك أداء الفحص الذاتي للثدي كان منخفضًا بشكل خاص بين مجتمع المرأة الليبية في مصراتة